The Effect of Marketing Communication on Purchasing Decisions of Elota Indonesia Screen-Printed T-Shirts - Rahmat Wahyudi; Andi Mappatompo; Ahmad AC (Yayasan Amerta Insan Unggul, 2026)
This study aims to examine the effect of marketing communication on purchasing satisfaction of Elota Indonesia screen-printed T-shirts. The research employed a quantitative approach using a survey method, with data collected through questionnaires distributed to 55 consumers of Elota Indonesia screen-printing products in Gowa Regency. The data were analyzed using simple linear regression with SPSS version 27. The results indicate that marketing communication (X) has a positive and significant effect on purchasing satisfaction (Y) of Elota Indonesia screen-printed T-shirts. This is evidenced by the t-test results, where the calculated t-value (10.486) exceeds the t-table value (1.674), with a significance level of 0.000 (< 0.05). Furthermore, the F-test results show that the calculated F-value (109.955) is greater than the F-table value (4.027), with a significance level of 0.000 (< 0.05), indicating that marketing communication simultaneously has a significant influence on consumer purchasing decisions. These findings highlight the important role of effective marketing communication in enhancing consumer satisfaction in the screen-printing industry.